A tool to identify recent or present rheumatoid arthritis flare from both patient and physician perspectives: The 'FLARE' instrument. Issue 7 (9th November 2011) - Berthelot, Jean-Marie; De Bandt, Michel; Morel, Jacques; Benatig, Fatima; Constantin, Arnaud; Gaudin, Philippe; Le Loet, Xavier; Maillefert, Jean-Francis; Meyer, Olivier; Pham, Thao; Saraux, Alain; Solau-Gervais, Elisabeth; et al.
Abstract : Introduction: There is a lack of consensus about the definition of flare of rheumatoid arthritis (RA) and a measurement tool. Objectives: To develop a self-administered tool integrating the perspectives of the patient and the rheumatologist, enabling the detection of present or recent-past RA flare. Methods: The patient perspective was explored by semistructured individual interviews of patients with RA. Two health psychologists conducted a content analysis to extract items best describing flare from the interviews. The physician's perspective was explored through a Delphi exercise conducted among a panel of 13 rheumatologists. A comprehensive list of items produced in the first round was reduced in a four-round Delphi process to select items cited by at least 75% of the respondents. The identified elements were assembled in domains—each converted into a statement—to constitute the final self-administered Flare Assessment in Rheumatoid Arthritis (FLARE) questionnaire. Results: The content of 99 patient interviews was analysed, and 10 domains were identified: joint swelling or pain, night pain, fatigue and different emotional consequences, as well as analgesic intake. The Delphi process for physicians identified eight domains related to objective RA symptoms and drug intake, of which only four were common to domains for patients. Finally, 13 domains were retained in the FLARE questionnaire, formulated as 13 statements with a Likert-scale response modality of six answers ranging from 'absolutely true' to 'completely untrue'. Conclusion: Two different methods, for patient and physician perspectives, were used to develop the FLARE self-administered questionnaire, which can identify past or present RA flare.